The Correlation of Critical Thinking Skill and Science Problem-Solving Ability of Junior High School Students - Irma Lismayani; Parno Parno; Susriyati Mahanal (Pascasarjana Universitas Negeri Malang (UM), 2017)
Abstract: This paper intends to seek the correlation of critical thinking skill and problem-solving ability of students on Natural Sciences Subject within Junior High School in Ecosystem topic. The subject of this research consisted of 135 students of 8th Graders in Odd Semester SMPN 17 Kendari Academic Year 2016/2017. This research employed two instruments, namely, critical thinking skill test in the form of multiple choices and problem-solving ability test in the form of an essay. The data obtained were then analyzed by calculating the average and employing correlational statistics. This research proves that students’ critical thinking skill average is 35.74, the problem-solving ability is 48.18, and the correlation coefficient is 0.31. It further means that only 9.61% of problem-solving ability could be explained by critical thinking ability. Key Words: critical thinking skill, problem-solving abilityAbstrak: Penelitian ini bertujuan untuk mengetahui hubungan kemampuan berpikir kritis dan kemampuan pemecahan masalah IPA siswa SMP pada topik Ekosistem. Subjek penelitian ini terdiri atas 135 siswa kelas VIII Semester I SMPN 17 Kendari tahun pelajaran 2016/2017. Penelitian ini menggunakan dua instrumen, yaitu tes kemampuan berpikir kritis berbentuk pilihan ganda dan tes kemampuan pemecahan masalah berbentuk esai. Data hasil penelitian dianalisis secara rata-rata dan statistik korelasi. Hasil penelitian menunjukkan bahwa siswa memiliki skor rata-rata kemampuan berpikir kritis 35,74, kemampuan pemecahan masalah 48,18 dan koefisien korelasi sebesar 0,31. Hal ini berarti hanya 9,61% kemampuan pemecahan masalah dapat dijelaskan oleh kemampuan berpikir kritis.Kata kunci: kemampuan berpikir kritis, kemampuan pemecahan masalah